The relative age effect in the Spanish elite male handball - Carlos Sánchéz Rodríguez; Álvaro Yáñez Sancho; Manuel Sillero Quintana; Jesús Rivilla-García (Federación Extremeña de Balonmano; University of Extremadura, 2012)
The birth in different quarters of the year involved differences regarding maturational development in handball players, which may influence the selection, development and consolidation in the elite in handball. This study sought to investigate the relative age effect in elite male handball players in Spain. To do this, data of birth and specific position of 586 players were analyzed, who participe in the League ASOBAL in seasons between 2003-04 and 2008-09. Comparisons and differences were studied by 2 tests and Z. Analysis of results revealed a higher percentage of players born in the first quarter, significant differences were confirmed in spanish players. Specifically, the highest percentages of players born in the first months of the year were the specific positions of the first offensive line and the goalkeeper. In conclusion, the results seem to confirm a relative effect of age on the players analyzed. The nationality and specific positions have a significant relationship with this. Keys words:  RAE, professional, birth date, detection, selection, talent.